Numerical approximation of nonlinear fluid-structure interaction problems - Sváček, Petr (Proceedings of the Conference Algoritmy, 2015)
This paper is concerned with the numerical approximation of nonlinear fluid- structure interaction problems, with a detailed description of numerical approximation of turbulent flow by stabilized finite element method. The interaction of flow with flexibly supported airfoil with aileron is numerically analyzed. The motion of the airfoil is described with the aid of system of ordinary differential equations (ODE) for three degrees of freedom coupled with the Reynolds Averaged Navier-Stokes system of equations completed by the turbulence model. The flow and structural problems are coupled via strong coupling algorithm. Numerical results showing the comparison of computation carried out by the k ¡ ! and Spalart-Allmaras methods are presented.